Peran Kader terhadap Peningkatan Keberhasilan Pemberian ASI Eksklusif di Wilayah Kerja Puskesmas Winong Kabupaten Purworejo - Nurma Ika Zuliyanti; Miftahu Rofingatul Karomah (LPPM Akbid Harapan Ibu Pekalongan, 2023)
The program for exclusive breastfeeding (ASI) is a priority program to address the prevalence of undernutrition and malnutrition. The Integrated Service Post (Posyandu) is an extension of the Puskesmas that provides health services and monitoring in an integrated manner. Posyandu as the spearhead of public health services has an important role in increasing exclusive breastfeeding and also continuing breastfeeding until the age of 24 months and monitoring growth and development from birth to 60 months of age. The role of cadres in organizing Posyandu is very large because apart from being a provider of health information to the community they are also a motivator for the community to come to Posyandu and carry out clean and healthy living behaviors, where exclusive breastfeeding is an indicator of PHBS. Rebug Village, Winong Health Center Work Area, has 3 Posyandu with 12 cadres. Data on breastfeeding mothers in Rebug Village are 24 people, with details of 6 people having babies 0-6 months, 7-11 months 2 people and 12-24 months 16 people. Of the 6 people who have babies aged 0-6 months, 5 of them give complementary foods with formula milk for work reasons. The aim of counseling is to measure the level of knowledge and understanding of Rebug Village cadres about exclusive breastfeeding and to measure the level of understanding of cadres about how to properly manage lactation. The result of counseling is an increase in knowledge and understanding of cadres after being given counseling on exclusive breastfeeding and lactation management.